Approaches to assess new pneumococcal vaccines for immunogenicity, development and licensure - Feroze A. Ganaie; Moon H. Nahm (Human Vaccines & Immunotherapeutics)
Pneumococcal conjugate vaccines (PCVs) have transformed the prevention of Streptococcus pneumoniae infections, yet challenges such as serotype replacement and vaccine escape demand their continual evaluation for improvement. This review outlines the core approaches used to assess pneumococcal vaccine efficacy, from early-stage development to licensure. The WHO-ELISA is the established method for quantifying serotype-specific IgG levels, while the opsonophagocytic assay assess functional antibody activity and serve as an independent correlate of protection across both vaccine and cross-reactive serotypes. Assessment of antibody avidity and memory B-cell responses offer additional insights into immune quality and durability. Together, these methodologies form a robust framework for evaluating current and next-generation PCVs, supporting evidence-based vaccine licensure, informing public health strategies, and addressing evolving challenges in pneumococcal disease prevention.